The influence of microwave radiation on the thermal stability of aluminum nanopowder; Technical Physics Letters; Vol. 42, № 4 - Mostovshchikov A. V. Andrey Vladimirovich; Ilyin A. P. Aleksandr Petrovich; Chumerin P. Yu. Pavel Yurievich; Yushkov Y. G. Yuri Georgievich; Vaulin V. A. Viktor Alekseevich; Alekseev B. A. Boris Aleksandrovich (2016, 2016)
Title screen